Official financing : recent developments and selected issues - Gilman, Martin G.; Wang, Jian-Ye.; International Monetary Fund. Policy Development and Review Dept. (Washington, D.C. : International Monetary Fund, 2003)
This book provides information on official financing and the debt situation of developing countries. It discusses issues related to trade finance in financial crisis and the challenge of maintaining external debt sustainability in debtor countries.
Overview -- Recent developments in export credits -- Financing from multilateral institutions -- Debt restructuring with official bilateral creditors -- Debt relief, new aid flows, and the challenge of maintaining external debt sustainability.
Includes bibliographical references (p. 89-90).
nmn 17/05/13
Loans
Keywords: International finance; Export credit; Debt relief; Debtor and creditor